2007
DOI: 10.1088/0029-5515/47/7/019
|View full text |Cite
|
Sign up to set email alerts
|

Integrated simulation of ELM energy loss determined by pedestal MHD and SOL transport

Abstract: Abstract. An integrated simulation code TOPICS-IB based on a transport code with a stability code for the peeling-ballooning modes and a scrape-off-layer (SOL) model has been developed to clarify self-consistent effects of edge localized modes (ELMs) and SOL on the plasma performance. Experimentally observed collisionality dependence of the ELM energy loss is found to be caused by both the edge bootstrap current and the SOL transport. The bootstrap current decreases with increasing the collisionality and inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…In the case A with P inped /P ped =0.21, the ELM energy loss is less than 10 % of the pedestal energy and is comparable with those in JT-60U [1]. As a reference, we add a result in the previous study [14], which indicated by A' in Fig.4. In the case A', values of τ ELM and χ max ELM are reduced half to τ ELM =200 µs and χ max ELM =100 m 2 /s, and the plasma current is reduced to I p =1.5 MA (q 95 =4.6).…”
Section: Simulation Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…In the case A with P inped /P ped =0.21, the ELM energy loss is less than 10 % of the pedestal energy and is comparable with those in JT-60U [1]. As a reference, we add a result in the previous study [14], which indicated by A' in Fig.4. In the case A', values of τ ELM and χ max ELM are reduced half to τ ELM =200 µs and χ max ELM =100 m 2 /s, and the plasma current is reduced to I p =1.5 MA (q 95 =4.6).…”
Section: Simulation Resultsmentioning
confidence: 89%
“…(a) ∆WELM /W ped versus P inped /P ped for ν* ped = 0.06 (A-D) and (b) ∆WELM /W ped versus ν* ped for P inped /P ped = 0.66 (C). Results in previous study [14] are shown by open symbols A'. In (b), shaded region denotes experimental data [1,2].…”
Section: Simulation Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The ranges of parameters covered in the PR08 discharges from JT-60U are 3.1m ≤ R ≤ 3.4m, 0.74m ≤ a ≤ 0.87m, 1.7T ≤ B t ≤ 4.3T, 0.53MA ≤ I p ≤ 1.8MA, 1.4 ≤ κ ≤ 1.77 and 0.05 ≤ δ ≤ 0.37, while the heating power is in the range 2.7MW ≤ P aux ≤ 25.5MW. All JT-60U discharges were analysed using the 1.5-dimensional transport code TOPICS (TOkamak Prediction and Interpretation Code System) [80,81], which reconstructed MHD equilibria using constraints from a motional Stark effect (MSE) diagnostic [82]. Heating and current drive from neutral beam injection and from electron cyclotron waves were respectively calculated using the OFMC (Orbit Following Monte Carlo) [83] and EC-Hamamatsu [84] codes.…”
Section: Jt-60umentioning
confidence: 99%
“…In order to study core and edge/pedestal regions, the integrated code TOPICS-IB [5] has been developed on the basis of the 1.5 dimensional (1.5 D) transport code TOP-ICS [6] extended to the integrated simulations for burning plasma. Plasma rotation is another important factor affecting the plasma confinement, the ITB/ETB formation and the RWM suppresstion, and its modeling requires the momentum transport, the formation of radial electric field, whose shear can suppress the turbulence, collisional and j × B torques.…”
Section: Introductionmentioning
confidence: 99%